On the Behavior of Solutions of Xenon in Liquid n-Alkanes: Solubility of Xenon in n-Pentane and n-Hexane - Bonifácio, Rui P. M. F. (2010)
The solubility of xenon in liquid n-pentane and n-hexane has been studied experimentally, theoretically, and by computer simulation. Measurements of the solubility are reported for xenon + n-pentane as a function of temperature from 254 to 305 K. The uncertainty in the experimental data is less than 0.15%. The thermodynamic functions of solvation such as the standard Gibbs energy, enthalpy, and entropy of solvation have been calculated from Henry’s law coefficients for xenon + n-pentane solutions and also for xenon + n-hexane, which were reported in previous work. The results provide a further example of the similarity between the xenon + n-alkane interaction and the n-alkane + n-alkane interactions. Using the SAFT-VR approach we were able to quantitatively predict the experimental solubility for xenon in n-pentane and semiquantitatively that of xenon in n-hexane using simple Lorentz−Berthelot combining rules to describe the unlikely interaction. Henry’s constants at infinite dilution for xenon + n-pentane and xenon + n-hexane were also calculated by Monte Carlo simulation using a united atom force field to describe the n-alkane and the Widom test particle insertion method.